2017
DOI: 10.4218/etrij.17.0116.0305
|View full text |Cite
|
Sign up to set email alerts
|

Network Intrusion Detection Based on Directed Acyclic Graph and Belief Rule Base

Abstract: Intrusion detection is very important for network situation awareness. While a few methods have been proposed to detect network intrusion, they cannot directly and effectively utilize semi-quantitative information consisting of expert knowledge and quantitative data. Hence, this paper proposes a new detection model based on a directed acyclic graph (DAG) and a belief rule base (BRB). In the proposed model, called DAG-BRB, the DAG is employed to construct a multi-layered BRB model that can avoid explosion of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…With the increasing probability of network security time, people gradually realize that network attacks and hacker attacks have brought great threats to people's daily life. Therefore, Zhang et al (2017) found that network situational awareness can effectively predict network intrusion [11], which is basically consistent with the results of this study that CS-RBF based network security situational awareness model can effectively predict attack and vulnerability information. DDos attack refers to that it can reasonably request resources from the server, thus occupying a variety of services so that users who normally request access can't get a response.…”
Section: Discussionsupporting
confidence: 88%
“…With the increasing probability of network security time, people gradually realize that network attacks and hacker attacks have brought great threats to people's daily life. Therefore, Zhang et al (2017) found that network situational awareness can effectively predict network intrusion [11], which is basically consistent with the results of this study that CS-RBF based network security situational awareness model can effectively predict attack and vulnerability information. DDos attack refers to that it can reasonably request resources from the server, thus occupying a variety of services so that users who normally request access can't get a response.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, it is impossible to execute physically perfect access control in an in-vehicle CAN. Although it is possible to find abnormal connections using an intrusion detection system (IDS), network IDS is a complex classification problem [30], so it is difficult to apply it to the vehicular ECUs.…”
Section: G Access Control Policymentioning
confidence: 99%
“…Zhang et al [2] divided methods for network intrusion detection into two types: direct methods using single algorithm and combination method by combination of several methods. The author proposed a new detection model based on a directed acyclic graph (DAG) and a belief rule base (BRB).…”
Section: A Deep Learning-based Intrusion Detectionmentioning
confidence: 99%